Estrategias psicopedagógicas para el fortalecimiento de habilidades sociales en estudiantes de séptimo año de egb en la escuela José Isaac Montes en el periodo 2024-2025 - Romero Vera, Keidy Jelitza (2025)
This research aimed to design a proposal of psychopedagogical strategies aimed at strengthening social skills in seventh-grade students of General Basic Education (EGB) at the José Isaac Montes School, during the 2024–2025 academic year. The study adopted a quantitative approach, with a non-experimental design, descriptive level, and basic research type. The sample consisted of 75 students from sections A, B, and C, who were assessed using Goldstein’s Social Skills Scale (1978), an instrument that evaluates six key dimensions of social behavior. The results showed that 48% of the students were at a low level of social skills, with notable difficulties in emotional expression, planning, and stress management. In response to this diagnosis, a proposal was developed based on six strategies: game-based learning, collaborative work, emotional intelligence, conflict resolution, relaxation techniques, and goal planning. The proposal was submitted to expert judgment, who evaluated its relevance, feasibility, sustainability, and educational impact positively. It is concluded that the proposal constitutes a valuable tool for strengthening school coexistence and the social development of students, being adaptable to similar contexts in basic education.